Aktivitas Antioksidan dan Antimalaria Senyawa Fenolik dari Daun Macaranga beccariana Merr. - Eva Marliana; Chairul Saleh; Medi Hendra (JURNAL KIMIA MULAWARMAN, 2018)
Macaranga beccariana Merr. is an endemic plant of Kalimantan which is no report yet about its biological activity and isolated compounds. Therefore, in order to know the potency of M. beccariana, determination of antioxidant and antimalarial activities along with isolation of bioactive compounds from this plant must be carried out. In this research, the leaves of M. beccariana was extracted using methanol to obtain methanol extract. Furthermore, the extract was separated and purified to obtain compound 1 and compound 2. Based on structure elucidation using spectrometer analysis including UV, 1H and 13C NMR, compounds 1 and 2 which belong to phenolics were identified as 4-hidroxybenzoic acid and 3,4-dihidroxybenzoic acid, respectively. Moreover, antioxidant activity using DPPH (2,2-diphenyl-1-picrylhydrazyl) and antimalarial activity towards Plasmodium falciparum strain 3D7 using Giemsa staining were performed. Rutine and chloroquine difosfat were used as positive controls for antioxidant and antimalarial, respectively. The results showed that the methanol extract of M. beccariana and its isolated compounds (1 and 2) are active for those activities. It can be concluded that the leaves of M. beccariana has good potency as antioxidant and antimalarial agents.